Lineage-level divergence of copepod glycerol transporters and the emergence of isoform-specific trafficking regulation - Catalán-García, Marc; Chauvigné, François; Stavang, Jon Anders; Nilsen, Frank; Cerdà, Joan; Finn, Roderick Nigel (Communications biology, 2021)
Transmembrane conductance of small uncharged solutes such as glycerol typically occurs through aquaglyceroporins (Glps), which are commonly encoded by multiple genes in metazoan organisms. To date, however, little is known concerning the evolution of Glps in Crustacea or what forces might underly such apparent gene redundancy. Here, we show that Glp evolution in Crustacea is highly divergent, ranging from single copy genes in species of pedunculate barnacles, tadpole shrimps, isopods, amphipods and decapods to up to 10 copies in diplostracan water fleas although with monophyletic origins in each lineage. By contrast the evolution of Glps in Copepoda appears to be polyphyletic, with surprisingly high rates of gene duplication occurring in a genera- and species-specific manner. Based upon functional experiments on the Glps from a parasitic copepod ( Lepeophtheirus salmonis ), we show that such lineage-level gene duplication and splice variation is coupled with a high rate of neofunctionalization. In the case of L. salmonis , splice variation of a given gene resulted in tissue- or sex-specific expression of the channels, with each variant evolving unique sites for protein kinase C (PKC)- or protein kinase A (PKA)-regulation of intracellular membrane trafficking. The combined data sets thus reveal that mutations favouring a high fidelity control of intracellular trafficking regulation can be a selection force for the evolution and retention of multiple Glps in copepods. Marc Catalán-Garcia et al. examine evolutionary divergence of aquaglyceroporins (GLPs) in copepods, observing that these genes are subject to high rates of gene duplication across species. They also report tissue- and sex-specific expression of GLP splice variants in the parasitic copepod, L. salmonis, that in turn exhibit PKA- or PKC-dependent changes in membrane trafficking. Altogether, these results suggest that mutations in GLP genes with precise regulation of intracellular tracking may be related to neofunctionalization in these species.